PEMBUATAN SELAI CAMPURAN DAMI NANGKA DAN SIRSAK - Sri Wahyuni; Vonny Setiaries Johan; Noviar Harun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to get the best formulation of mix jackfruit rags and soursop in making fruit jam. This research used Complete Randomized Design (CRD) with four treatments and four replications, followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatments in this research were DS1 (jam with mix jackfruit rags pulp 65% and soursop pulp 35%), DS2 (jam with mix jackfruit rags pulp 50% and soursop pulp 50%), DS3         (jam with mix jackfruit rags pulp 35% and soursop pulp 65%), DS4 (jam with mix jackfruit rags pulp 20% and soursop pulp 80%). The result of analysis showed that the jackfruit rags and soursop significantly affected the moisture content, total acid content, total dissolved solids,  sucrose content, fiber content, description of sensory test on colour, texture, flavour, taste and overall test. The best formulation of jam was DS2 (jam with mix jackfruit rags pulp 50% and soursop pulp 50%) with moisture content 25.25%; total acid content 4.66; total dissolved solids 67.91obrix,  sucrose content 54.74%; fiber content 2.85%. Description of sensory test scores of DS2 (jam with mix jackfruit rags pulp 50% and soursop pulp 50%) were colour 3.66 (yellow), taste 3.17 (taste jackfruit rags and soursop), texture 3.31 (soft) and flavour 3.83 (jackfruit rags and soursop flavour). Overall scores of DS2 were colour 4.05 (like), taste 4.05 (like), texture 4.06 (like), flavour 3.94 (like) and over all test 4.31 (like).Keywords: Jam, jackfruit rags, soursop.